The effect of community based tourism in Batu Puteh Kinabatangan Borneo: based on value co-creation on subjective wellbeing / Nik Rozilaini Wan Mohamed and Nurfatin Nabihah Faisal - Wan Mohamed, Nik Rozilaini; Faisal, Nurfatin Nabihah (Universiti Teknologi MARA, Sabah, 2023)
This study examines the effect of community-based tourism in Batu Puteh, Kinabatangan, Borneo based on a new study gap variable known as value co-creation on subjective wellbeing. In recent years, there has been a growing interest in community-based tourism as a sustainable development approach that empowers local communities and fosters social responsibility. The problem statement of this study lies in the need for evaluation and understanding of the impact of community-based tourism in Batu Puteh, Kinabatangan, Borneo, on wellbeing, specifically in terms of value co-creation. Specifically, there is a need to assess how community-based tourism contributes to the overall wellbeing of the local community by examining the co-creation of values between tourists and community members. The sample size of this study consists of 284 respondents from the community at Batu Puteh Village. The research method used in this study is quantitative, which involves collecting and analyzing numerical data. Analysis using SEM Amos to examine the relationship between community-based tourism benefited the perceived costs, value co-creation, and subjective wellbeing. The findings of this study contribute to the existing body of knowledge on community-based tourism and its impact on wellbeing. The perceived costs were found not significant in influencing the value co-creation process between tourists and community members in Batu Puteh, Kinabatangan, Borneo. However, overall findings found that community-based tourism in Batu Puteh, Kinabatangan, Borneo, has a positive impact on the wellbeing of the local community.